OPPORTUNITIES TO IMPROVE THE EFFICIENCY OF RESERVOIR USE IN THE NARYN-SYRDARYA BASIN (Scientific journal of the Fergana State University, 2026)
This article explores opportunities to improve the efficiency of water use in the Syr Darya-Naryn rivers under the Toktagul Reservoirs energy-producing mode. The paper primarily examines the reservoirs filled with water from the Syr Darya and Naryn rivers and their economic importance. Under the conditions of operation of the Toktagul reservoir in the energy regime, the possibilities of increasing the capacity of the reservoirs of the Syrdarya-Naryn basin for the effective use of the large non-vegetative runoff observed in the lower reaches of the river are evaluated. Recommendations are given on improving the efficiency of using river water resources in conditions of unfavorable water regime in the lower reaches of the Naryn River.